Branching crypts in inflammatory bowel disease revisited. Issue 3 (17th November 2021) - Rubio, Carlos A.; Schmidt, Peter T.; Lang‐Schwarz, Corinna; Vieth, Michael
Abstract: Histologic sections from patients with inflammatory bowel disease (IBD) usually exhibit crypts with architectural distortions and branching crypts. It has been postulated that crypt branching should be assessed only in well‐oriented, upright crypts. However, those crypts are mostly found in sections from colectomy specimens and colon mucosectomies. Sections from endoscopic biopsies are fortuitously cut in a horizontal plane, a procedure mostly revealing cross‐cut crypt rings. In endoscopic biopsies from UC patients we previously detected cross‐cut crypts heralding the crest domain of branching crypts. Recently, the scrutiny of biopsies from IBD patients revealed that branching‐crest domains concurred either with crypts in symmetric branching, typified by twin, amalgamating back‐to‐back isometrics crypt‐rings, or with crypts in asymmetric branching, characterized by ≥2 amalgamating anisometric crypt‐rings; both symmetric and asymmetric branching‐crest domains were encased by a thin muscularis mucosae . Quantitative studies in biopsies from Swedish and German patients with IBD showed that crypts in asymmetric branching outnumbered those in symmetric branching. Because crypt‐branching seldom occurs in the normal colon in adults and considering that colon crypts typically divide once or twice during a lifetime, the accruing of asymmetric branching crypts in IBD biopsies emerges as a significant histologic parameter. Although the biological significance of asymmetric crypt‐branching in IBD remains at present elusive, their occurrence deserves to be further investigated. The future policy will be to include in our pathologic reports, the number of crypts in asymmetric branching, in order to monitor their frequency in prospective surveillance biopsies in patients with IBD.